Computer-based simulation of plasma concentration time-profiles of drug in nonlinear two-compartment model - Piekarski, Sławomir; Kiełczyński, Piotr; Szalewski, Marek; Rewekant, Mirosław (Computer Assisted Methods in Engineering and Science, 2017)
The main interest of pharmacokinetics is the study of the fate of drugs in the living organism. This work proposes the system of the conservation laws that describes time-dependent concentrations of a drug, after a single intravenous administration. Compared with others, the proposed model considers both free and protein-bound drug concentrations at the same time. Plasma protein binding captured in the model enters the nonlinearity arising from the Guldberg-Waage law. According to our best knowledge, the analytical solution for our system does not exist. Our model allows the calculation of the free and bound-drug protein concentrations at any time point and at any dose after single intravenous bolus dose administration. In order to compare the empirical with simulated data, a numerical approach has been proposed. On the basis of published experimental data the model validation has been carried out. The goodness of fit was satisfactory ( R ² = 0.99) and the experimental and simulated AUC (area under the curve) values, as the measure of the bioavailability of drug, were similar (150 M/hxh - ¹). The preliminary assessment of the model credibility was positive and encouraged further studies.